Patients' experiences of communication and involvement in decision‐making about atrial fibrillation treatment in consultations with nurses and physicians. Issue 3 (28th December 2015) - Siouta, Eleni; Hellström Muhli, Ulla; Hedberg, Berith; Broström, Anders; Fossum, Bjöörn; Karlgren, Klas
Abstract : Background: Insights in consultations across patient interactions with physicians and nurses are of vital importance for strengthening the patients' involvement in the treatment decision‐making process. The experience of involvement and communication in decision‐making from the patients' perspective has been sparsely explored. Objective: To examine how patients describe involvement in and communication about decision‐making regarding treatment in consultations with nurses and physicians. Method: Twenty‐two patients with atrial fibrillation (AF), aged 37–90 years, were interviewed directly after their consultations with nurses and physicians in outpatient AF clinics in six Swedish hospitals. Results: In consultations with nurses, the patients felt involved when obtaining clarifications about AF as a disease and its treatment and when preparing for and building up confidence in decision‐making. In consultations with physicians, the patients felt involved when they could cooperate in decision‐making, when acquiring knowledge, and when they felt that they were being understood. One shared category was found in consultations with both nurses and physicians, and the patients felt involved when they had a sense of trust and felt secure during and between consultations. Conclusions: Patients with AF stated that they would need to acquire knowledge and build up confidence and ability in order to be effectively involved in the decision‐making about treatment. Despite not being actively involved in decision‐making, patients felt involved through experiencing supportive and confirming communication. Practice implications: Attention must be given to the relationship with the patient to create the conditions for patient involvement in the consultation. This can be achieved through supportive communication attempting to create a feeling of clarity and building confidence. This will support involvement in decision‐making concerning AF treatment and feelings of being understood and of trust in physicians and/or nurses.